The Cpx Stress Response Regulates Turnover of Respiratory Chain Proteins at the Inner Membrane of Escherichia coli - Tsviklist, Valeria; Guest, Randi L.; Raivio, Tracy L. (Frontiers in Microbiology, 2022)
The Cpx envelope stress response is a major signaling pathway monitoring bacterial envelope integrity, activated both internally by excessive synthesis of membrane proteins and externally by a variety of environmental cues. The Cpx regulon is enriched with genes coding for protein folding and degrading factors, virulence determinants, and large envelope-localized complexes. Transcriptional repression of the two electron transport chain complexes, NADH dehydrogenase I and cytochrome bo3, by the Cpx pathway has been demonstrated, however, there is evidence that additional regulatory mechanisms exist. In this study, we examine the interaction between Cpx-regulated protein folding and degrading factors and the respiratory complexes NADH dehydrogenase I and succinate dehydrogenase in Escherichia coli. Here we show that the cellular need for Cpx-mediated stress adaptation increases when respiratory complexes are more prevalent or active, which is demonstrated by the growth defect of Cpx-deficient strains on media that requires a functional electron transport chain. Interestingly, deletion of several Cpx-regulated proteolytic factors and chaperones results in similar growth-deficient phenotypes. Furthermore, we find that the stability of the NADH dehydrogenase I protein complex is lower in cells with a functional Cpx response, while in its absence, protein turnover is impaired. Finally, we demonstrated that the succinate dehydrogenase complex has reduced activity in E. coli lacking the Cpx pathway. Our results suggest that the Cpx two-component system serves as a sentry of inner membrane protein biogenesis, ensuring the function of large envelope protein complexes and maintaining the cellular energy status of the cell.